A patent review of two fruitful decades (1997-2016) of Isocoumarin research. (2nd November 2017) - Hussain, Hidayat; Green, Ivan R
ABSTRACT: Introduction : Isocoumarins comprise a six-membered oxygen heterocycle (α-pyranone) along with one aromatic ring and are known to possess interesting biological properties. During the last two decade (1997–2016), isocoumarin chemistry has attracted attention due to its biological and pharmaceutical effects viz., anticancer, anti-diabetic, antibacterial, antimalarial, and fungicidal effects. Areas covered : This review covers the patents on the therapeutic activities of natural and synthetic isocoumarins over the last two decades (1997–2016). Moreover a number of international patents related to natural and synthetic isocoumarins along with their biological effects will be presented and discussed. Although a large number of patents have been published during the period of the review, the aim of this review is to focus on those important patents specifically related to microbial diseases, cancer, malaria, and diabetes. Expert opinion : Isocoumarin and its synthetic analogs display a wide range of important pharmaceutical properties. Furthermore, isocoumarins have the potential to conjugate with other anticancer drugs which will synergistically increase the delivery and thus anticancer effects. Moreover, in order to get lead compounds, scientists should focus on the synthesis of halo and functionalized heterocyclic ring containing derivatives of isocoumarins as more potent drugs.